The exchange rate, asymmetric shocks and asymmetric distributions - Calin-Vlad Demian; Filippo di Mauro (European Central Bank (ECB), 2015)
The elasticity of exports to exchange rate fluctuations has been the subject of a large literature without a clear consensus emerging. Using a novel sector level dataset based on firm level information, we show that exchange rate elasticities double in size when the country and sector specific firm productivity distribution is taken into account in empirical estimates. In addition, exports appear to be sensitive to appreciation episodes, but rather unaffected by depreciations. Finally, only rather large changes in the exchange rate appear to matter.
Keywords: F14; F41; F31; 330; bilateral trade; exchange rate elasticity; productivity dispersion; TFP